138k views
0 votes
What is f(g(x)) if f(x)is


(2)/(x - 3)
And g(x) is

(2)/(x) + 3
and also what is g(f(x))?

User Birarduh
by
5.7k points

1 Answer

4 votes

\bf \begin{cases} f(x)=\cfrac{2}{x-3}\\\\ g(x)=\cfrac{2}{x}+3 \end{cases} \\\\\\ f(~~g(x)~~)=\cfrac{2}{g(x)-3}\implies f(~~g(x)~~)=\cfrac{2}{(2)/(x)+3 -3} \\\\\\ f(~~g(x)~~)=\cfrac{2}{(2)/(x)}\implies f(~~g(x)~~)=\cfrac{\quad (2)/(1)\quad }{(2)/(x)} \\\\\\ f(~~g(x)~~)=\cfrac{2}{1}\cdot \cfrac{x}{2} \implies \boxed{f(~~g(x)~~)=x}


\bf g(~~f(x)~~)=\cfrac{2}{f(x)}+3\implies g(~~f(x)~~)=\cfrac{2}{(2)/(x-3)}+3 \\\\\\ g(~~f(x)~~)=\cfrac{(2)/(1)}{(2)/(x-3)}+3\implies g(~~f(x)~~)=\cfrac{2}{1}\cdot \cfrac{x-3}{2}+3 \\\\\\ g(~~f(x)~~)=x-3+3\implies \boxed{g(~~f(x)~~)=x}
User JP Alioto
by
5.6k points